Analisis Strategi Guru dalam Meningkatkan Pemahaman Belajar Siswa Autisme di SMP Zainul Hasan 1 Genggong - Silvi Rizqiyah; Hifdil Islam; Popy Rachman (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
Education is an important forum and means for society and the entire community has the right to receive proper education in developing human resources in the learning process as a long-term provision. The aim of this research is to find out the role of a class assistant teacher or homeroom teacher, subject teacher and special support teacher. in improving the learning understanding of autistic students at SMP Zainul Hasan1 Ganggong. This research uses a qualitative method with a descriptive approach to collecting data from various written sources, observation, interviews and documentation. In this research, the researcher uses a case study methodology which requires a thorough examination of an event, where the researcher carries out data collection, data reduction, data presentation, which includes collection, reduction, presentation and drawing conclusions, triangulation to verify the validity of the data. The results of this research show that there is an initiative strategy from the class assistant teacher, including the strategic involvement of subject teachers and the strategy of guidance and counseling teachers as special assistants who can improve the learning understanding of students with special needs as well as educate and train them in improving social and communication skills. The results of this research can be concluded that treatment for students with autism is by providing special guidance and motivating autistic students' interest in learning.